(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2013)
Results are presented of the vegetation study of the former Tarutinskyi military polygon (sq. 24521,19 ha). For the first time ever a vegetation map has been compiled, setting the ground for further monitoring of the vegetation. Information is given upon the main syntaxa of vegetation on the site, their dynamics. A specific of the vegetation of the territory is the predomination of the plant communities Bothriochloeta ischaemi. Rather quick increase the territories occupied by the Stipeta lessingianae and Stipeta capillatae communities are observed, that means of the active processes of steppe restoration. Nature value of the Tarutinskyu steppe and a necessity of its conservation as the regional landscape park (sq. 5200 ha) have been substantiated.